Photoelectric conversion element material, method for producing the photoelectric conversion element material, and ink containing dispersed semiconductor nanoparticles

AgBiS2 and Ag2S nanoparticles are used to create a light-receiving layer with enhanced near-infrared responsiveness, addressing the limitations of conventional materials by improving photoresponsivity and stability in photoelectric conversion elements.

JP7621387B2Active Publication Date: 2025-01-24TANAKA KIKINZOKU KOGYO KK +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022574021
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-06
Filing Date
2021-12-27
Publication Date
2025-01-24
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

Existing semiconductor materials struggle to provide effective responsiveness to near-infrared light, particularly due to the lack of common low bandgap semiconductor materials and challenges in forming practical devices with high photoresponse characteristics.

Method used

Development of AgBiS2 and Ag2S semiconductor nanoparticles with a band gap of 1 eV or less, which are used to form a light-receiving layer in a photoelectric conversion element, with a crystallite diameter of 10-25 nm and a surface roughness of 2-15 nm, enhancing near-infrared light absorption and responsiveness.

Benefits of technology

The resulting photoelectric conversion element material exhibits improved responsiveness to near-infrared light, suitable for applications such as LIDAR and SWIR image sensors, outperforming conventional materials like PbS in photoresponsivity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621387000003
    Figure 0007621387000003
  • Figure 0007621387000004
    Figure 0007621387000004
  • Figure 0007621387000005
    Figure 0007621387000005
Patent Text Reader

Abstract

The present invention pertains to a photoelectric conversion element material comprising: a base material; and a light receiving layer composed of a semiconductor film formed on the base material. The semiconductor film forming the light receiving layer is composed of Ag2-xBixSx+1 (x is an integer of 0 or 1), and has a crystallite diameter of 10-40 nm. The light receiving layer can be produced by applying ink, obtained by dispersing the semiconductor nanoparticles in a dispersion medium, to the base material and then firing the ink at 200-350ºC. A photoelectric conversion element material according to the present invention has absorption properties with respect to light having wavelengths in a near-infrared range, and has excellent photoresponsivity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photoelectric conversion element material used in an optical sensor, etc. In particular, the present invention relates to a photoelectric conversion element material having a light-receiving layer made of a predetermined metal chalcogenide on a substrate. The present invention also relates to an ink in which semiconductor nanoparticles are dispersed, which is suitable for forming the light-receiving layer of the photoelectric conversion element material. [Background technology]

[0002] Semiconductor nanoparticles called quantum dots (QDs) are expected to be used as a component material of photoelectric conversion elements and light-emitting elements mounted on various optical semiconductor devices such as solar cells, optical sensors, and light-emitting devices (LEDs). When semiconductors are made into nanoscale particles, they exhibit a quantum confinement effect and show a band gap according to the particle size. Therefore, by controlling the composition and particle size of semiconductor nanoparticles to adjust the band gap, it becomes possible to arbitrarily set the emission wavelength and absorption wavelength.

[0003] Semiconductor nanoparticles can contribute to the miniaturization and thinning of semiconductor devices that have photoelectric conversion elements as light-receiving elements. For example, silicon photodiodes are used in the photoelectric conversion parts of CMOS image sensors that have traditionally been installed in video cameras, mobile phone cameras, etc. In these CMOS image sensors, a silicon thin film of a certain thickness (2 to 3 μm) is required to absorb the light required to drive the sensor. On the other hand, semiconductor nanoparticles have the properties of having high quantum efficiency and a high absorption coefficient. This makes it possible to make the thickness of the light-receiving elements of CMOS image centers thinner (less than 1 μm) than with existing technology.

[0004] The characteristic of semiconductor nanoparticles, that is, the emission and absorption wavelengths can be adjusted, can be the starting point for the development of photoelectric conversion elements that can handle light in wavelength ranges that were difficult to handle with conventional semiconductor materials. In particular, there has been a demand in recent years for the development of photoelectric conversion elements that are responsive to light in the near-infrared region. Examples of photoelectric conversion elements that use near-infrared light include light receiving elements applied to LIDAR (Light Detection and Ranging) and near-infrared (SWIR) image sensors. LIDAR is a remote sensing system used in automatic driving of automobiles, drones, ships, etc. LIDAR is a measurement system that irradiates a target with laser light, detects the reflected light with a light receiving element, and detects the distance and angle to the target. LIDAR can be said to be an important device in the recent development of automatic driving technology. SWIR image sensors are also a device that is expected to see increased demand in the future in fields such as food inspection, agriculture, and drones.

[0005] Photoelectric conversion elements such as the LIDAR and SWIR image sensors exemplified above require good response characteristics to light in the near-infrared region. In this regard, it has been difficult for conventional semiconductor materials to meet this requirement. Silicon used in the above-mentioned CMOS image sensors has difficulty responding to near-infrared light due to its band gap value. Therefore, the effectiveness of semiconductor nanoparticles is expected from the perspective of responding to such near-infrared light. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-40847 A [Patent Document 2] JP 2020-15802 A Summary of the Invention [Problem to be solved by the invention]

[0007] At present, there are not many reports of semiconductor nanoparticles that are responsive to light in the near-infrared region. Even if the band gap of semiconductor nanoparticles can be adjusted by controlling the particle size, the adjustable range is based on the band gap of the semiconductor material that constitutes the nanoparticles. Here, based on the photon energy formula (E=hc / λ (h: Planck's constant, c: speed of light, λ: wavelength)), in order to obtain responsiveness in the near-infrared light region (wavelength range of 700 nm to 2500 nm), the band gap of the semiconductor nanoparticles needs to be approximately 1.77 eV or less. However, there are not many semiconductor materials with such a low band gap.

[0008] Metal chalcogenides, which are binary or ternary compounds of one or two transition metals (Pb, Cd, etc.) and chalcogen elements excluding oxygen (S, Se, Te, etc.), are known as semiconductor materials constituting semiconductor nanoparticles. In particular, PbS is known as a metal chalcogenide that has responsiveness to near-infrared light when made into semiconductor nanoparticles and has been put to practical use. However, since PbS contains Pb, it is difficult to say that it is a suitable semiconductor material due to recent environmental issues. Therefore, it is necessary to consider the structure and composition of semiconductor materials that meet this requirement.

[0009] Even if a metal chalcogenide having a response characteristic to near-infrared light is found and the semiconductor nanoparticles are produced, it is necessary to study the formation of a device material having a practical high photoresponse characteristic. In order to apply the semiconductor nanoparticles to a photoelectric conversion device, the semiconductor nanoparticles are dispersed in a suitable dispersion medium to form an ink (dispersion liquid), which is then applied to a substrate to form a semiconductor thin film that serves as a light receiving layer. In order to improve the response characteristic of a photoelectric conversion device to near-infrared light, the characteristics of the semiconductor nanoparticles are important, but the characteristics of the semiconductor thin film formed as described above are even more important.

[0010] The present invention has been made under the above-mentioned background, and aims to propose semiconductor nanoparticles made of metal chalcogenide having light absorption in the near-infrared region, and to provide a photoelectric conversion element material having a light-receiving layer with excellent light response, which is made of a semiconductor thin film formed from the semiconductor nanoparticles. The present invention also clarifies an ink containing the semiconductor nanoparticles, and a method for producing a semiconductor thin film of a suitable configuration using the ink. [Means for solving the problem]

[0011] In order to solve the above problems, the present inventors first investigated the composition of metal chalcogenides that have a suitable band gap and can exhibit responsiveness in the near-infrared region when made into semiconductor nanoparticles. The present inventors then focused on Ag-based chalcogenides AgBiS2 and Ag2S. Since the band gap of these Ag-based chalcogenides is 1 eV or less in the bulk state, it is believed that making them into semiconductor nanoparticles can exhibit responsiveness to near-infrared light.

[0012] Therefore, the inventors have confirmed the near-infrared light absorption of each of the semiconductor nanoparticles of AgBiS2 and Ag2S, and have confirmed that these semiconductor nanoparticles can be made into ink in a suitable state, and further that it is possible to form a semiconductor thin film that serves as a light-receiving layer. Based on these studies, the inventors have conducted a study on the composition of thin films with improved responsiveness to near-infrared light for AgBiS2 thin films and Ag2S thin films formed from semiconductor nanoparticles, and have arrived at the present invention.

[0013] The present invention for solving the above problems provides a photoelectric conversion element material comprising a substrate and a light receiving layer made of a semiconductor film formed on the substrate, the semiconductor film being made of Ag 2-x Bi x S x+1 (x is an integer of 0 or 1), and the crystallite diameter of the semiconductor film is 10 nm or more and 25 nm or less.

[0014] The configuration of the photoelectric conversion element material having a light-receiving layer made of a metal chalcogenide thin film according to the present invention and the method for producing the same will be described below. As described above, the photoelectric conversion element material according to the present invention is basically composed of a substrate and a light-receiving layer on the substrate.

[0015] A. Configuration of the photoelectric conversion element material according to the present invention A-1 Base material The substrate is a member for supporting the light receiving layer made of a metal chalcogenide semiconductor film. Any material may be used for the substrate as long as it can fulfill this purpose. Examples of the substrate material include glass, quartz, silicon, ceramics, and metal. The shape and dimensions of the substrate are not particularly limited.

[0016] A-2 Light-receiving layer (a) Composition of the light-receiving layer The semiconductor film constituting the light receiving layer of the photoelectric conversion element material according to the present invention is Ag-based metal chalcogenide. 2-x Bi x S x+1 (x is 0 or 1), that is, a thin film made of AgBiS2 or Ag2S. Since the band gaps of these metal chalcogenides in the bulk state are 0.8 eV (AgBiS2) and 0.9 eV (Ag2S), which are less than 1 eV, it is believed that nanoparticles of these metal chalcogenides have responsiveness in the near-infrared region.

[0017] (b) Structure of the light-receiving layer The light-receiving layer made of a semiconductor film is a thin film formed by depositing nanoparticles of AgBiS2 or Ag2S. In the present invention, the crystallite diameter of the semiconductor nanoparticles of AgBiS2 or Ag2S in the thin film is specified in order to improve the light response. The crystallite diameter is the maximum region that can be regarded as a single crystal in the semiconductor nanoparticles. The semiconductor nanoparticles in the thin film of the present invention are polycrystalline or single crystalline, and the crystallite diameter is smaller than or equal to the particle diameter of the semiconductor nanoparticles. In the present invention, the crystallite diameter of AgBiS2 or Ag2S is set to 10 nm or more and 40 nm or less. In the light-receiving layer made of a semiconductor of the present invention, the reason why the light response is related to the crystallite diameter is unclear, but the present inventors presume that the crystal structure of AgBiS2 or Ag2S is optimized by increasing the crystallinity. When the crystallite diameter of AgBiS2 or Ag2S is less than 10 nm, the crystallinity is low and there is no difference from the state before the thin film is formed (the state of the semiconductor nanoparticles in the ink), and there is no improvement effect on the light response. On the other hand, in a thin film in which the crystallite size of AgBiS2 or Ag2S exceeds 40 nm, it is considered that the AgBiS2 particles or Ag2S particles are coarsened or the compound is partially decomposed, and in this case, the photoresponse is also decreased. The crystallite size of AgBiS2 and Ag2S is more preferably 10 nm or more and 25 nm or less.

[0018] Since the crystallite size is the smallest unit that can contribute to the diffraction of a substance when irradiated with X-rays, it can be measured by X-ray diffraction (XRD). When the crystallite size of the light-receiving layer of the present invention is measured by XRD, AgBiS2 has diffraction peaks at 2θ=27° and 31° using CuKα radiation. Ag2S has diffraction peaks at 2θ=26° and 38° using CuKα radiation. In the present invention, it is preferable to measure the crystallite size based on the diffraction peaks at 2θ=31° for AgBiS2 and 2θ=38° for Ag2S. As described later, in the present invention, the crystallite size can be adjusted by heat-treating a thin film of AgBiS2 or Ag2S at a predetermined temperature. In AgBiS2 and Ag2S, the peak at 2θ=38° can be clearly confirmed at any heat treatment temperature. The crystallite size can be calculated by calculating the half-width of the diffraction peak and based on the Scherrer formula.

[0019] The surface roughness of the light-receiving layer of the photoelectric conversion element material according to the present invention is preferably 2 nm or more and 15 nm or less. It is believed that an increase in surface roughness affects the interparticle distance. In a photoelectric conversion element, since the interparticle distance affects the efficiency of electron exchange between particles, it is preferable to set the surface roughness within the above range. Furthermore, the thickness of the light-receiving layer made of a semiconductor thin film is preferably 10 nm or more.

[0020] The photoelectric conversion element material according to the present invention has absorptivity and responsiveness to light in the near-infrared region, preferably to light in the near-infrared region having a wavelength of 700 nm or more and 1200 nm or less. This characteristic is due to the band gap of AgBiS2 or Ag2S, which is a semiconductor forming the absorption layer.

[0021] Therefore, the photoelectric conversion element material according to the present invention is applied to semiconductor devices that handle light with wavelengths in the near-infrared region, and the applications are not particularly limited. For example, it can be used as a semiconductor material for a wide range of applications, such as light receiving elements, optical sensors, and photodetectors. In particular, since it has excellent light receiving sensitivity in the near-infrared region, it is suitable for light receiving elements such as LIDAR and SWIR image sensors.

[0022] B. Method for producing the photoelectric conversion element material according to the present invention In the manufacture of the photoelectric conversion element material according to the present invention, it is necessary to form a semiconductor thin film (AgBiS2 thin film or Ag2S thin film) that will become a light receiving layer on the above-mentioned base material. In the present invention, the AgBiS2 thin film or Ag2S thin film is formed by applying an ink in which semiconductor nanoparticles are dispersed. In addition, in order to set the crystallite size of the above-mentioned semiconductor in a suitable range, the semiconductor layer after application is baked and a treatment is performed to increase the crystallinity. These characteristic parts will be described below.

[0023] B-1 Semiconductor nanoparticle ink according to the present invention In the present invention, an ink in which semiconductor nanoparticles are dispersed in a dispersion medium is used. 2-x Bi x S x+1 (x is 0 or 1). These semiconductor nanoparticles dispersed in the ink have a particle size of 3 nm or more and 20 nm or less, and a crystallite diameter of 3 nm or more and 20 nm or less. The particle size of the semiconductor nanoparticles is specified in this way in order to have a band gap in the near-infrared light region while maintaining the quantum confinement effect of the quantum dots. And since the crystallite diameter is the maximum value in the region in which the semiconductor nanoparticles can be regarded as single crystals, it can be said that it is preferable for it to be as large as possible within the particle size range.

[0024] Semiconductor nanoparticles are dispersed in a dispersion medium while protected by a protective agent. Protective agents are additives that suppress the aggregation and coarsening of semiconductor nanoparticles and stabilize the dispersion state. Aggregation and coarsening of semiconductor nanoparticles must be avoided because they affect the response characteristics when applied to a substrate to form a light-receiving layer. Protective agents are organic compounds that bind to semiconductor nanoparticles and suppress the aggregation of nanoparticles due to repulsion between the protective agents.

[0025] The protective agent of the ink according to the present invention is composed of at least one of a long-chain alkylamine, a long-chain carboxylic acid, and a thiol. Specifically, the long-chain alkylamine is a linear or branched alkylamine having 6 or more carbon atoms. Specific preferred alkylamines include octylamine (8 carbon atoms), decylamine (10 carbon atoms), dodecylamine (12 carbon atoms), tetradecylamine (14 carbon atoms), and oleylamine (18 carbon atoms). The carboxylic acid is a linear or branched carboxylic acid having 6 or more carbon atoms. Specific preferred carboxylic acids include octanoic acid (8 carbon atoms), lauric acid (12 carbon atoms), myristic acid (14 carbon atoms), and oleic acid (18 carbon atoms). The thiol is a linear or branched thiol having 6 or more carbon atoms. Specific preferred thiols include octanethiol (8 carbon atoms), dodecanethiol (12 carbon atoms), and octadecanethiol (18 carbon atoms). The above long-chain alkylamines, carboxylic acids and thiols can be used in combination as a protecting agent.

[0026] The dispersion medium of the semiconductor nanoparticle ink is an organic solvent with low polarity, specifically, toluene, hexane, chloroform, dichloromethane, cyclohexane, octanol, or other single solvent or a mixture of these solvents is preferred.

[0027] The semiconductor nanoparticle ink of the present invention can be produced by synthesizing AgBiS2 and Ag2S nanoparticles in advance and dispersing them in a dispersion medium. AgBiS2 nanoparticles are synthesized by adding sulfur or a sulfur compound to a mixed solution in which an Ag salt (e.g., silver acetate, silver oxalate, silver nitrate, silver carbonate, silver diethyldithiocarbamate, etc.) and a Bi salt (bismuth acetate, bismuth nitrate, etc.) are mixed together with a protective agent, and reacting the mixture to synthesize AgBiS2 nanoparticles bound to a protective agent. Ag2S nanoparticles can be synthesized by mixing and reacting the same Ag salt as above with a sulfur compound (thiourea, sulfur) together with a protective agent. Any of the nanoparticles can be separated from the reaction solution after synthesis, appropriately washed, and then added to a dispersion medium to form an ink.

[0028] B-2 Method for forming a light-receiving layer on a substrate (ink application and baking process) The ink in which the semiconductor nanoparticles are dispersed is applied to a substrate and then baked to form a light-receiving layer made of the semiconductor film of the present invention. The ink is preferably applied by spin coating in order to deposit the semiconductor nanoparticles uniformly on the substrate. This ink is preferably applied two or more times. As for the application conditions, the rotation speed is preferably 500 to 5000 rpm and the rotation time is preferably 10 to 300 seconds.

[0029] In the present invention, a baking process is performed after the application of the ink of semiconductor nanoparticles to obtain a semiconductor nanoparticle light-receiving layer having suitable light response. In this baking process, the crystallinity of the semiconductor nanoparticles (AgBiS2 nanoparticles, Ag2S nanoparticles) on the substrate is increased by heating, and the crystallite size is set to the above-mentioned suitable range. The baking temperature at this time is 200°C or more and 350°C or less. If the temperature is less than 200°C, the crystallite size does not fall within the specified range, and the effect of improving the response is small. In addition, since the protective agent adsorbed on the particle surface does not volatilize sufficiently, the charge around the particle is biased, and the quantum confinement effect is inhibited. By setting the baking temperature at 200°C or more, the crystallinity is improved and the effect of improving the response is expected. At this time, although there is a possibility that a small amount of the protective agent remains on the particle surface, the amount of the protective agent that can inhibit the quantum confinement effect has been removed. On the other hand, as for the upper limit of the baking temperature, if it exceeds 350°C, the crystallite size becomes large due to excessive crystallization. In addition, there is a risk of Ag precipitation due to decomposition of the compound, destruction of the semiconductor film due to the generation of compounds deviating from the desired chemical composition, etc. This baking treatment is preferably carried out in an inert gas (nitrogen, argon, etc.), and the treatment time is preferably 0.5 hours or more.

[0030] It is more preferable that the baking temperature after coating the ink of semiconductor nanoparticles is 200°C or higher, up to 250°C. Even baking at 250°C or higher is expected to improve the optical response from the viewpoint of crystallinity. However, especially for AgBiS2, baking at 250°C or higher exceeds the three-phase eutectic point, and the semiconductor particles melt once, which may affect the stability of the film.

[0031] Through the above-mentioned firing process, an absorption layer made of a semiconductor thin film having a predetermined crystallite size is formed. Then, by appropriately forming wiring that enables electrical connection with the absorption layer, a photoelectric conversion element can be formed. Effect of the Invention

[0032] As described above, the present invention relates to a metal chalcogenide, Ag 2-x Bi x S x+1 (x is an integer of 0 or 1). This light-receiving layer is composed of semiconductor nanoparticles of the metal chalcogenide, and has light responsiveness in the near-infrared region. In particular, by setting the crystallite size of the light-receiving layer made of a semiconductor within a predetermined range, the responsiveness to light in the near-infrared region is improved. [Brief description of the drawings]

[0033] [Figure 1] TEM image of AgBiS2 nanoparticles produced in the first embodiment. [Diagram 2] FIG. 2 shows an XRD diffraction pattern of the AgBiS2 nanoparticles produced in the first embodiment. [Diagram 3] FIG. 2 shows the results of DSC analysis of the AgBiS2 nanoparticles produced in the first embodiment. [Figure 4] FIG. 11 is a graph showing the light absorption characteristics of the AgBiS2 ink produced in the first embodiment. [Diagram 5] FIG. 2 is a diagram showing an XRD diffraction pattern of the surface of the absorption layer of the photoelectric conversion element manufactured in the first embodiment. [Figure 6]4 is a photograph showing the results of observation, by AFM, of the surface morphology of the surface of the absorption layer of the photoelectric conversion element manufactured in the first embodiment. [Figure 7] FIG. 4 is a diagram showing the PL measurement results of each photoelectric conversion element manufactured in the first embodiment. [Figure 8] 4 is a graph showing the results of an evaluation test of the light response of each photoelectric conversion element manufactured in the first embodiment. [Figure 9] 1 is a graph comparing the PL measurement results of photoelectric conversion elements manufactured at firing temperatures of 200° C. and 500° C. [Figure 10] 1 is a graph comparing the photoresponse of photoelectric conversion elements manufactured at firing temperatures of 200° C. and 500° C. [Figure 11] 4 is a graph comparing the photoelectric conversion element (200° C., 300° C.) manufactured in the first embodiment with a PbS light receiving layer. [Figure 12] 4 is a graph showing the results (high bias) of an evaluation test of the photoresponsiveness of each photoelectric conversion element manufactured in the first embodiment. [Figure 13] TEM image of Ag2S nanoparticles produced in the second embodiment. [Figure 14] FIG. 13 shows an XRD diffraction pattern of Ag2S nanoparticles produced in the second embodiment. [Figure 15] FIG. 11 is a graph showing the light absorption characteristics of the Ag2S ink produced in the second embodiment. [Figure 16] FIG. 13 is a diagram showing an XRD diffraction pattern of the surface of the absorption layer of the photoelectric conversion element manufactured in the second embodiment. [Figure 17] 13 is a photograph showing the results of observation, by AFM, of the surface morphology of the surface of the absorption layer of the photoelectric conversion element produced in the second embodiment. [Figure 18] FIG. 11 is a diagram showing the PL measurement results of each photoelectric conversion element manufactured in the second embodiment. [Figure 19] 13 is a graph showing the results of an evaluation test of the light response of each photoelectric conversion element manufactured in the second embodiment. [Figure 20] 1 is a graph comparing the PL measurement results of photoelectric conversion elements manufactured at firing temperatures of 200° C. and 500° C. [Figure 21] 1 is a graph comparing the photoresponse of photoelectric conversion elements manufactured at firing temperatures of 200° C. and 500° C. [Figure 22] 13 is a graph comparing a photoelectric conversion element (200° C., 300° C.) manufactured in the second embodiment with a PbS light receiving layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] First embodiment Hereinafter, an embodiment of the present invention will be described. In this embodiment, a photoelectric conversion element material having a light-receiving layer made of AgBiS2 as a semiconductor material was manufactured. Semiconductor nanoparticles of AgBiS2 were synthesized to form an ink, which was then applied to a substrate and baked to form a light-receiving layer, thereby manufacturing a photoelectric conversion element material. Thereafter, the morphology of the thin film that would become the light-receiving layer was observed, and the photoresponse characteristics of the photoelectric conversion element were evaluated.

[0035] [Preparation of AgBiS2 ink] 133.5 mg of silver acetate (Ag(OAc)), 386 mg of bismuth acetate (Bi(OAc)3), and 5.5 mL of oleic acid were mixed, and after replacing the inside of the mixing container with N2 gas, the mixture was stirred at 100°C for 1 hour. 5 mL of oleylamine in which 33 mg of sulfur was dissolved was added to react. The mixture was left to cool during the reaction. After that, AgBiS2 nanoparticles were separated and extracted with acetone, and the extract was centrifuged to recover the AgBiS2 nanoparticles. Furthermore, the recovered nanoparticles were mixed with toluene, and extracted and centrifuged again with acetone to recover the AgBiS2 nanoparticles. This was added to toluene, which is a dispersion medium, to make ink (nanoparticle concentration 0.04M). This ink was black.

[0036] [Measurement of particle size and crystallite size of AgBiS2 nanoparticles] The particle size and crystallite size of the AgBiS2 nanoparticles in the ink produced above were examined. In this study, the AgBiS2 nanoparticles were observed using a transmission electron microscope (TEM) to measure the particle size (average particle size). The AgBiS2 nanoparticles from the ink were then supported on SiO2 powder and measured in a dry state. The XRD analyzer was an Ultima IV manufactured by Rigaku Corporation, with the characteristic X-rays being CuKα rays and the analysis conditions being 0.1° / min.

[0037] FIG. 1 is a TEM image of the AgBiS2 nanoparticles produced in this embodiment. It was confirmed that nanoparticles of uniform particle size were produced, and image analysis (binary image analysis using ImageJ software) showed that the average particle size was 8.75 nm. FIG. 2 shows the XRD diffraction pattern of the AgBiS2 nanoparticles. Based on the diffraction peak near 2θ=31°, the crystallite size of the AgBiS2 nanoparticles was calculated to be 7.2 nm from the half-width.

[0038] [Thermal behavior of AgBiS2 nanoparticles] Next, differential scanning calorimetry (DSC) was performed on the AgBiS2 nanoparticles. The results are shown in Figure 3. A heat peak was observed at around 110°C due to the volatilization of the remaining solvent, and at around 160°C due to the desorption of the protective agent. This suggests that the excess protective agent was sufficiently volatilized below 200°C. In addition, a large endothermic peak was detected at around 250-260°C. This is thought to be a peak derived from the three-phase eutectic point of AgBiS2.

[0039] [Absorption properties of AgBiS2 nanoparticles] In order to confirm the optical semiconductor properties of the AgBiS2 nanoparticles produced in this embodiment, the light absorption properties were evaluated. The above ink was diluted 100 times, and the light absorption properties were analyzed using an ultraviolet-visible-near infrared spectrophotometer (UV-Vis-NIR spectrophotometer: UV-3600i Plus manufactured by Shimadzu Corporation).

[0040] The absorption spectrum of the AgBiS2 ink is shown in Figure 4. It was confirmed that the absorption edge of this AgBiS2 ink extends to a wavelength range exceeding 1000 nm, and that it is capable of absorbing light in the near-infrared region.

[0041] [Formation of the light-receiving layer] After confirming the above characteristics of the AgBiS2 nanoparticles and ink, the ink was applied to a substrate to form a light receiving layer, and a photoelectric conversion element material was manufactured. A silicon wafer (dimensions: 25×25, thickness 0.6 mm) was prepared as the substrate, and the above ink was applied to the substrate. The ink was applied by a spin coating method, and the ink was dropped onto the substrate and applied at a rotation speed of 2000 rpm (30 seconds) to form a semiconductor layer. In this embodiment, this application process was repeated three times, and the amount of application per time was 0.1 mL (mass of nanoparticles: 2.8 mg).

[0042] After applying the AgBiS2 ink, the light-receiving layer was formed by baking. The baking was performed in a nitrogen atmosphere at seven different temperatures: 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, and 500°C. The treatment time was 0.5 hours.

[0043] [Measurement of crystallite size and surface roughness of the light-receiving layer (XRD, AFM)] For the seven types of photoelectric conversion elements manufactured by the above seven firing patterns, the semiconductor thin film constituting the light-receiving layer was analyzed by XRD and the crystallite size was calculated. The XRD analysis was performed by measuring the thin film directly on the silicon wafer. It was performed using the same equipment and conditions as the analysis of nanoparticles. In addition, an atomic force microscope (AFM: Nanocute, Hitachi High-Tech Science Corporation) was used to image the surface morphology of the light-receiving layer and measure the surface roughness.

[0044] Figure 5 shows the XRD diffraction patterns of the light-receiving layer surface of the seven types of photoelectric conversion elements. When observing the diffraction peaks around 27° in this diffraction pattern, it is confirmed that the peak intensity increases with increasing sintering temperature, and a sharp peak with a narrow half-width appears. This shows that crystallinity improves when the sintering temperature is increased. Therefore, the crystallite diameter was calculated based on the diffraction peak around 31°, and the following value was obtained. Figure 6 shows the observation results of the light-receiving layer surface morphology using an AFM. The results of the surface roughness measurement using an AFM are shown in Table 1.

[0045] [Table 1]

[0046] From Table 1, it can be seen that the crystallite size of the thin film increases with increasing temperature of the calcination process. In particular, the crystallinity improves at temperatures above 200°C. However, when the calcination temperature reaches 500°C, the peak near 31° is burned away and the peak derived from pure Ag near 38.3° becomes clear, indicating that decomposition of AgBiS2 occurs at this calcination temperature.

[0047] In addition, looking at the relationship between the firing temperature and the surface roughness of the thin film, there is no change in the surface roughness at firing temperatures up to 200°C, but the surface roughness increases between 250°C and 300°C, and then returns to the original surface roughness at 300°C to 350°C. This is considered to be related to the fact that the AgBiS2 nanoparticles were dissolved once during firing at a temperature exceeding the three-phase eutectic point of AgBiS2 (around 250 to 260 °C) confirmed by the DSC analysis of the AgBiS2 nanoparticles described above. Therefore, it can be said that there is no perfect proportional relationship between the firing temperature and the surface roughness. However, when the firing temperature exceeds 400 °C, the surface roughness increases sharply, and the AgBiS2 particles become coarse. This point coincides with the fact that the diffraction peak near 27 ° rises sharply at 400 °C in the XRD diffraction profile. And, when firing at 500 °C, the AgBiS2 particles become islanded, even though the surface roughness decreases due to the decomposition of AgBiS2.

[0048] [Photoluminescence measurement] After confirming the above-mentioned configuration of the light receiving layer, photoluminescence (PL) measurement was performed as a preliminary evaluation of the optical semiconductor properties of the photoelectric conversion element material manufactured in this embodiment. Here, the measurement was performed using a photoelectric conversion element material manufactured through baking treatment at 150°C, 200°C, and 300°C. The PL measurement was performed using LabRam Aramis manufactured by Horiba Ltd. as a measuring device, and the measurement conditions were a range of 500 to 1000 nm.

[0049] The PL measurement results for each photoelectric conversion element material are shown in Figure 7. Considering the previous XRD measurement results, it can be seen that PL increases as the crystallinity of the thin film improves through baking at 200°C or higher.

[0050] [Evaluation of photoresponse characteristics] The photoresponse characteristics were evaluated for the photoelectric conversion element material manufactured in this embodiment. In this evaluation test, the photoelectric conversion element material manufactured through baking treatment at 150°C, 200°C, and 300°C was used, and a sample was prepared by patterning a Ti film (film thickness 5 nm) and an Au film (film thickness 40 nm) in this order into a comb shape on the surface of each light receiving layer by thermal evaporation to form an electrode. Then, a bias voltage of 0.5 V was applied with a multimeter connected to the electrode, and the photocurrent associated with pulse irradiation of the near-infrared light source was measured. The wavelengths of the near-infrared light were 740 nm, 850 nm, and 940 nm, and the pulse irradiation of the near-infrared light was 20 seconds ON / 40 seconds OFF.

[0051] The photocurrent measurement results are shown in Figure 8. It can be seen that an improvement in photoresponse was observed in the AgBiS2 thin film in which the crystallite diameter of the thin film was adjusted by baking at 200°C or higher. In this test, particularly favorable photocurrent amplification was observed in the sample (crystallite diameter 13.77 nm) that had been baked at 200°C.

[0052] Furthermore, to confirm the effect of sintering temperatures exceeding 350°C, PL measurements and photoresponse evaluations were performed on the absorption layer prepared by sintering at 500°C. These results are shown in Figures 9 and 10, in comparison with the absorption layer prepared by sintering at 200°C. The PL measurement results in Figure 9 show that the emission peak has almost disappeared in the AgBiS2 thin film sintered at 500°C. Furthermore, the photocurrent measurement results in Figure 10 show that the AgBiS2 thin film sintered at 500°C shows almost no photoresponse. When the AgBiS2 thin film sintered at 500°C was analyzed by SEM-EDS, the crystal structure of AgBiS2 was broken and the presence of particles was confirmed.

[0053] Here, in this embodiment, a comparison was made with a photoelectric conversion element having a light receiving layer of a PbS thin film, which is conventionally known as a metal chalcogenide thin film having sensitivity in the near infrared region. An ink was prepared by dispersing commercially available PbS particles (Sigma-Aldrich) and was applied to the same substrate as in this embodiment. Then, an evaluation test of the light response was performed in the same manner as described above.

[0054] The results are shown in Fig. 11 together with the photoelectric conversion element of this embodiment (baking temperatures 150°C, 200°C, and 300°C). In the photoelectric conversion element with PbS as the light receiving layer, the generation of photocurrent is observed to some extent, but the photoelectric conversion element (200°C, 300°C) with the AgBiS2 thin film as the light receiving layer of this embodiment generates a higher photocurrent than this conventional technology. Therefore, it is clear that the photoelectric conversion element according to the present invention has an advantage over the conventional technology.

[0055] Next, the photoresponse characteristics of the photoelectric conversion element were evaluated when the bias during photocurrent measurement was set to a high bias. In this evaluation, a commercially available Ag nanopaste was applied to the surface of the light receiving layer by screen printing, and a comb-shaped wiring with a thickness of about 1 μm was formed to prepare a sample. A bias voltage of 2.0 V was then applied using a multimeter connected to the electrodes, and the photocurrent associated with pulse irradiation of a near-infrared light source was measured. The wavelengths of the near-infrared light were 850 nm and 940 nm, and the pulse irradiation of the near-infrared light was 10 seconds on / 10 seconds off.

[0056] The results of this photoresponse evaluation test are shown in Figure 12. Figure 12 shows that the photoresponse under high bias showed a significant increase in photocurrent, especially in the thin films (crystallite diameters 22.32 nm and 21.29 nm) fired at 300°C and 350°C.

[0057] Second embodiment In this embodiment, a photoelectric conversion element material having a light receiving layer made of Ag2S as a semiconductor thin film was manufactured. As in the first embodiment, after synthesizing Ag2S semiconductor nanoparticles and manufacturing ink, the ink was applied to a substrate and baked to manufacture the photoelectric conversion element material.

[0058] [Preparation of Ag2S ink] 134 mg of silver acetate, 30.5 mg of thiourea, 11.8 mL of oleylamine, and 0.2 mL of dodecanethiol were mixed and the mixture was stirred at 200°C for 10 minutes to react. After the reaction, the mixture was left to cool. Then, the Ag2S nanoparticles were separated and extracted with methanol, and the extract was centrifuged to recover the Ag2S nanoparticles. The recovered nanoparticles were mixed with toluene, and extracted and centrifuged again with methanol to recover the Ag2S nanoparticles. This was added to toluene, which is a dispersion medium, to make ink (nanoparticle concentration 0.04M). This ink was light brown and transparent.

[0059] [Measurement of particle size and crystallite size of Ag2S nanoparticles] The particle size and crystallite size of the Ag2S nanoparticles in the ink produced above were examined. Particle size (average particle size) measurement was performed by TEM and XRD analysis was performed under the same conditions as in the first embodiment.

[0060] Figure 13 is a TEM image of Ag2S nanoparticles produced in this embodiment. It was confirmed that nanoparticles of uniform particle size were produced, and the average particle size was 14.86 nm. Figure 14 shows the XRD diffraction pattern of AgBiS2 nanoparticles. Based on the diffraction peak near 2θ=38°, the crystallite size of the Ag2S nanoparticles was calculated to be 17.2 nm from the half-width.

[0061] [Absorption properties of Ag2S nanoparticles] The results of measuring the light absorption characteristics of Ag2S ink using a method similar to that of the first embodiment are shown in Fig. 15. It was confirmed that the absorption edge of Ag2S ink also extends to a wavelength region exceeding 1000 nm, and that it is capable of absorbing light in the near-infrared region.

[0062] [Formation of the light-receiving layer] After the above-mentioned investigations, the Ag2S ink was applied to a substrate to form a light-receiving layer, and a photoelectric conversion element material was manufactured. As in the first embodiment, the ink was applied to a silicon wafer, which is a substrate. The ink was applied in the same manner as in the first embodiment. After the Ag2S ink was applied, a baking process was performed to form a light-receiving layer, as in the first embodiment. The baking process was performed in a nitrogen atmosphere at temperatures of 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, and 500°C.

[0063] [Measurement of crystallite size and surface roughness of the light-receiving layer (XRD, AFM)] For the seven types of photoelectric conversion element materials of this embodiment, the semiconductor thin film constituting the light-receiving layer was subjected to XRD analysis and the crystallite size was calculated. In addition, the surface morphology of the light-receiving layer was imaged and the surface roughness was measured using an atomic force microscope.

[0064] Figure 16 shows the XRD diffraction patterns of the absorption layer surface of each photoelectric conversion element material. Figure 17 shows the results of AFM observation of the absorption layer surface morphology. Table 2 shows the crystallite size and surface roughness values ​​calculated based on the diffraction peak at about 38° in the XRD diffraction patterns.

[0065] [Table 2]

[0066] The particle behavior of the absorption layer made of the Ag2S thin film of this embodiment by the calcination process is basically the same as that of the absorption layer made of the AgBiS2 thin film of the first embodiment. That is, as the temperature of the calcination process increases, the crystallite size of the thin film increases, but when the calcination temperature becomes high, Ag2S decomposes. In this embodiment, the peak of Ag2S around 38° when calcined at 150°C is so small that the crystallite size cannot be calculated. In addition, in the relationship between the calcination temperature and the surface roughness of the thin film, the surface roughness does not change at a relatively low calcination temperature, but the surface roughness increases at calcination at 250°C or higher, and it is presumed that a change in the crystal structure occurs here as well. Then, calcination at 500°C causes decomposition of Ag2S and island formation of Ag2S particles.

[0067] [Photoluminescence measurement] Furthermore, the PL measurement results of the photoelectric conversion element material having a light receiving layer made of Ag2S manufactured in this embodiment are shown in Figure 18. It can be seen that in this embodiment as well, the PL increases as the crystallinity of the thin film improves due to the baking treatment.

[0068] [Evaluation of photoresponse characteristics] The photoresponse characteristics were evaluated for the photoelectric conversion element material having the light receiving layer made of Ag2S manufactured in this embodiment. Here, the photocurrent was measured for the photoelectric conversion element manufactured through baking treatment at 150°C, 200°C, and 300°C under the same sample and measurement conditions as those for the photocurrent measurement under low bias conditions (0.5 V) in the first embodiment.

[0069] The photocurrent measurement results of a photoelectric conversion element having an absorption layer made of Ag2S are shown in Fig. 19. In this embodiment as well, particularly good photocurrent amplification was observed in the sample (crystallite diameter 13.26 nm) that had been subjected to a sintering treatment at 200°C. The same was true for the absorption layer made of AgBiS2 in the first embodiment, but it was confirmed that the absorption layer sintered at 200°C or higher exhibited clearer photoresponsiveness than the absorption layer sintered at 150°C.

[0070] Furthermore, in this embodiment, the absorption layer made of Ag2S prepared by baking at 500°C was subjected to PL measurement and photoresponse evaluation. These results are shown in Fig. 20 and Fig. 21. From the PL measurement result in Fig. 20, it was found that the emission peak disappeared in the Ag2S thin film baked at 500°C. And, from the photoresponse evaluation result in Fig. 21, it was confirmed that the Ag2S thin film baked at 500°C showed almost no photoresponse. From the SEM-EDS analysis of the Ag2S thin film baked at 500°C in this embodiment, it was confirmed that the Ag2S composition had collapsed.

[0071] FIG. 22 shows a comparison between the absorption layer made of Ag2S of this embodiment and the absorption layer made of PbS of the prior art. Compared with AgBiS2 of the first embodiment, Ag2S is not as superior to PbS as AgBiS2. However, at 740 nm and 850 nm, Ag2S has a higher photocurrent value than PbS. In this regard, AgBiS2 of the first embodiment showed an extremely better optical response than PbS even in the 940 nm region, and therefore is expected to be more applicable as a near-infrared light receiving element. [Industrial Applicability]

[0072] As described above, the photoelectric conversion element material according to the present invention has a light receiving layer made of a metal chalcogenide, Ag. 2-x Bi x S x+1 (x is an integer of 0 or 1). By imparting appropriate crystallinity to this absorption layer, it exhibits excellent responsiveness to light in the near-infrared region. The present invention is particularly useful as a photoelectric conversion thin film for the light receiving element of various optical semiconductor devices, and is expected to contribute to the miniaturization and performance improvement of such devices as a light receiving element for LIDAR and image sensors.

Claims

1. A photoelectric conversion element material comprising a substrate and a light receiving layer made of a semiconductor film formed on the substrate, The semiconductor film is AgBiS 2 It consists of: The crystallite diameter of the semiconductor film is 10 nm or more and 25 nm or less, A photoelectric conversion element material, characterized in that the surface roughness of the semiconductor film is 9.05 nm or more and 15 nm or less.

2. 2. The photoelectric conversion element material according to claim 1, which has a responsiveness to light having a wavelength of 700 nm or more and 1200 nm or less.

3. A method for producing the photoelectric conversion element material according to claim 1 or 2, comprising the steps of: A step of applying an ink in which semiconductor nanoparticles are dispersed in a dispersion medium onto a substrate to form a semiconductor layer; and baking the semiconductor layer to form a light-receiving layer. the semiconductor nanoparticles of the ink are made of AgBiS 2 and have a crystallite diameter of 5 nm or more and 20 nm or less; the semiconductor nanoparticles are protected with a protecting agent comprising at least one of a long-chain alkylamine, a long-chain carboxylic acid, and a thiol; the dispersion medium of the ink is a low polarity organic solvent, The method for producing a photoelectric conversion element material, wherein the firing temperature in the step of firing the semiconductor layer is 250° C. or higher and 300° C. or lower.

Citation Information

Patent Citations

  • Silver-bismuth-sulfur thin film photoelectric detector and preparation method thereof

    CN110911568A

  • Semiconductor photosensitizer AgBiS2 quantum dot and preparation method thereof

    CN110950383A

  • Photovoltaic material and use thereof in photovoltaic device

    JP2017028267A

  • Ink and light-emitting element

    JP2020015802A

  • Semiconductor nanoparticle

    JP2020040847A